Pengaruh Employee Engagement dan Work Life Balance terhadap Kepuasan Kerja pada Pegawai Kantor Pertanahan Kota Depok (Jurnal Manajemen Kreatif dan Inovasi, 2025)
This study investigates the impact of Employee Engagement and Work-Life Balance on Job Satisfaction among employees at the Depok City Land Office. The research employed purposive sampling to select participants, and data were collected directly through questionnaires distributed to the respondents. All research instruments underwent rigorous validity and reliability testing, confirming that the items were appropriate for further statistical analysis. Using multiple linear regression analysis, the study found that both Employee Engagement and Work-Life Balance significantly and positively influence Job Satisfaction, both individually and collectively. The results suggest that employees who are highly engaged in their work and who successfully manage a balance between professional responsibilities and personal life tend to experience higher levels of job satisfaction. The coefficient of determination (R²) of 0.567 indicates that 56.7% of the variability in Job Satisfaction can be explained by these two independent variables, while the remaining variation is attributable to other factors not covered in this study. These findings provide empirical support for the importance of fostering Employee Engagement and creating a supportive work environment that promotes Work-Life Balance as effective strategies for enhancing overall employee satisfaction. Practically, this research offers valuable insights for organizational management, particularly in designing reward systems, implementing career development programs, and establishing policies that help employees balance their work and personal lives. By focusing on these strategies, organizations can sustainably improve employee productivity, commitment, and loyalty.